The influence of bus and taxi drivers' public self-consciousness and social anxiety on aberrant driving behaviors. (August 2018) - Huang, Yu-Wen; Lin, Pei-Chun; Wang, Jenhung
Highlights: The study examined bus and taxi drives' self-consciousness (PSC), social anxiety (SA) and aberrant driving behaviors (ADB). Bus drivers reported less ADB than did taxi drivers and female drivers reported less ADB than did their male counterparts. Female drivers reported higher PSC than did male drivers. Drivers with crash involvement in the past three years reported higher PSC than those without that involvement. Raising the PSC of bus drivers and drivers without crash involvement within three years will lead to reducing their ADB. Abstract: The study examined how bus and taxi drivers' public self-consciousness interacted with social anxiety to influence their aberrant driving behaviors. Questionnaires were distributed to 331 male and female Taiwanese bus and taxi drivers whose working environment involves frequent and direct interaction with passengers. Questionnaire statements measured drivers' dispositional public self-consciousness and social anxiety, and their intentions and driving behaviors related to speeding, errors and violations. The study utilized a mediating model and path analysis explored causal relationships between the constructs. The study found that both public self-consciousness and social anxiety explained bus drivers' aberrant driving behaviors. Female drivers reported less aberrant driving behaviors than their male counterparts did. Bus drivers reported less aberrant driving behaviors than taxi drivers. Drivers with crash involvement within three years reported higher public self-consciousness than did those without that involvement. The suitable research frameworks, which describe the influence of public self-consciousness and social anxiety on aberrant driving behaviors, fit to bus and taxi drivers are different, so as different to male and female drivers. The study findings suggest bus and taxi driver should receive special training in general attitude as a condition of their employment in order to avoid aggressive behaviors and provide a better and safer service to the public.